2015
DOI: 10.1007/s00464-015-4237-3
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the use of a transanal drainage tube to prevent anastomotic leakage after anterior resection by double-stapling technique for rectal cancer

Abstract: Placement of a TDT is an effective and safe procedure that can decrease the rate of anastomotic leakage and re-operation after an anterior resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 44 publications
1
33
1
Order By: Relevance
“…It has been reported that a DS reduces symptomatic AL, and a DS should be fashioned in rectal cancer patients with anastomoses below 6 cm, particularly in men [23][24][25] . The findings of this study might differ from previous results because a transanal tube was placed, which has been found to reduce the rate of AL after Lap-LAR [15,20,[26][27][28] . However, AL still occurred in patients who had a transanal tube placed.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…It has been reported that a DS reduces symptomatic AL, and a DS should be fashioned in rectal cancer patients with anastomoses below 6 cm, particularly in men [23][24][25] . The findings of this study might differ from previous results because a transanal tube was placed, which has been found to reduce the rate of AL after Lap-LAR [15,20,[26][27][28] . However, AL still occurred in patients who had a transanal tube placed.…”
Section: Discussioncontrasting
confidence: 56%
“…Therefore, in order to reduce the pressure in the rectum near the anastomotic line, the transanal tube could be kept in place for >7 days postoperatively in patients whose fecal volume for 3 days after surgery was ≥ 118 mL. A transanal tube can also localize peritonitis following AL, allowing the AL to be treated conservatively without the need for re-operation [15,20] . However, in patients with a fecal volume <118 mL for 3 days after surgery, there should be no issues if the transanal tube is removed at POD 4.…”
Section: Discussionmentioning
confidence: 99%
“…Such major complications have also not been reported in other studies. 11,13 We did not routinely perform a CT examination to check for anastomotic leakage in this study because of the cost and concerns over radiation exposure. We believed that colorectal anastomotic leakage would cause clinical symptoms even if the patient had a diverting stoma.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that AL rate was 3.6% in 28 patients with tube in comparison with 24.4% without tube replacement. The other two studies reported that procedure was effective and safe to prevent AL after colorectal cancer surgery with DST reconstruction [7,8]. Generally, to perform DST technique, the rectum was divided horizontally.…”
Section: Discussionmentioning
confidence: 99%